2017
DOI: 10.3390/medicines4020021
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Essential Oils against Pathogens Responsible for Otitis Externa in Dogs and Cats

Abstract: Background: Essential oils (EOs) are recommended by some veterinarians to treat otitis externa in pets, but data about their efficacy in scientific literature are very scant. Methods: Nine commercial EOs, from roman chamomile (Anthemis nobilis L.), star anise (Illicium verum), lavender (Lavandula hybrida), litsea (Litsea cubeba (Lour.) Pers.), basil (Ocimum basilicum L.), oregano (Origanum vulgare L. subsp. hirticum), rosemary (Rosmarinus officinalis L.), clary sage (Salvia sclarea L.), and thyme (Thymus vulga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 20 publications
6
45
3
1
Order By: Relevance
“…In this study, both oregano oil and thyme oil showed good antimicrobial activity against Gram‐negative and Gram‐positive bacteria as well as M. pachydermatis with MIC 90 values ranging from 0.02 to 0.25% (200–2,292 μg/mL). These results are in agreement with previous studies including oregano oil and thyme oil as potential antimicrobial agents against a broad range of bacteria; however, these studies mostly used the disk diffusion technique and presented the MIC values. In the present study, the antimicrobial activities of the essential oils and their phenolic components are reported as MIC range, MIC 50 and MIC 90 values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, both oregano oil and thyme oil showed good antimicrobial activity against Gram‐negative and Gram‐positive bacteria as well as M. pachydermatis with MIC 90 values ranging from 0.02 to 0.25% (200–2,292 μg/mL). These results are in agreement with previous studies including oregano oil and thyme oil as potential antimicrobial agents against a broad range of bacteria; however, these studies mostly used the disk diffusion technique and presented the MIC values. In the present study, the antimicrobial activities of the essential oils and their phenolic components are reported as MIC range, MIC 50 and MIC 90 values.…”
Section: Discussionsupporting
confidence: 92%
“…Thyme oil and oregano oil, and their main component have been reported for antimicrobial activities against both bacteria and fungi . One study determined antimicrobial activity for these essential oils against microbes associated with otitis externa in animals . However, to the best of the authors’ knowledge, no study has looked at their main phenolic components against a range of common clinical otitis externa microbes, including sensitive and resistant strains.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by the current increase in the transmission of antimicrobial-resistant pathogens from animals to humans, this study aimed to undertake preliminary screening of the antimicrobial activity of cinnamon oil and cinnamaldehyde against 31 strains, including ATCC strains and resistant clinical pathogens responsible for canine diseases, such as pyodermas, septicaemia, meningitis, urological infections, otitis externa and pneumoniae. (Duquette and Nuttall 2004;Lamm et al 2009;Jayanthi and Jeya 2014;Ebani et al 2017). Our results showed that both compounds exhibited promising antimicrobial activity against all pathogens tested, including bactericidal activity at their MICs except for Staphylococcus sp.…”
Section: Discussionsupporting
confidence: 51%
“…; Jayanthi and Jeya ; Ebani et al . ). Our results showed that both compounds exhibited promising antimicrobial activity against all pathogens tested, including bactericidal activity at their MICs except for Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, another positive effect of EOs in treatment could be their additional antibacterial effect. This was already shown in vitro against several bacterial veterinary isolates [34,36,48,65,66]. In addition, EOs can exhibit anti-inflammatory potential [67], which might be another positive attribute for treatment of otitis externa.…”
Section: Discussionmentioning
confidence: 71%